1985
DOI: 10.1161/01.str.16.4.643
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced in vivo platelet activation in subtypes of ischemic stroke.

Abstract: It remains uncertain whether platelet activation in ischemic stroke is contributory or secondary to brain ischemia. The efficacy of aspirin (ASA) in stroke prevention suggests that platelet activation contributes to the occurrence of stroke. On the other hand, platelet activation may be simply a generalized consequence of cerebral ischemic damage. To examine this issue, plasma levels of the platelet specific proteins beta-thromboglobulin (beta-TG) and platelet factor 4 (PF4) were measured in fifty-eight patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 18 publications
(6 reference statements)
5
70
1
Order By: Relevance
“…In contrast, Lip et al showed that there was a small but significant reduction in TG with conventional warfarin therapy (INR 1.5-2.5), although very low-dose warfarin or aspirin did not change the TG concentration. 4 Many studies have shown no significant changes in PF4 or TG with aspirin, [25][26][27] a consistent finding with the present results, but some studies have reported a significant reduction of TG with aspirin. 28,29 A possible explanation for the lack of significant decreases in PF4 and TG by antiplatelet treatment may be that different pathways activate the release of PF4 and TG and the inhibition of one pathway may not be enough to reduce the plasma concentrations of PF4 and TG.…”
Section: Effects Of Antiplateletssupporting
confidence: 90%
“…In contrast, Lip et al showed that there was a small but significant reduction in TG with conventional warfarin therapy (INR 1.5-2.5), although very low-dose warfarin or aspirin did not change the TG concentration. 4 Many studies have shown no significant changes in PF4 or TG with aspirin, [25][26][27] a consistent finding with the present results, but some studies have reported a significant reduction of TG with aspirin. 28,29 A possible explanation for the lack of significant decreases in PF4 and TG by antiplatelet treatment may be that different pathways activate the release of PF4 and TG and the inhibition of one pathway may not be enough to reduce the plasma concentrations of PF4 and TG.…”
Section: Effects Of Antiplateletssupporting
confidence: 90%
“…29 £-Thromboglobulin concentrations in both NVAF groups and platelet factor 4 concentration in the NVAF group with stroke were significantly increased, indicating platelet activation. Shah et al 30 studied groups of patients with thromboembolic and cardioembolic stroke and showed higher concentrations of /3-thromboglobulin in both groups but increased platelet factor 4 concentration only in thromboembolic stroke patients compared with matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Blood vessel occlusion is primarily caused by thrombosis (53% of cases) or embolism (31% of cases) (5). Thrombus formation can be caused by excessive platelet generation (6), and the association between platelets and ischemic stroke has been widely studied (7)(8)(9). Platelets are involved in both normal hemostasis and thrombosis (10).…”
Section: Introductionmentioning
confidence: 99%